Konstruksi religiositas tubuh dalam puisi Indonesia - Tengsoe Tjahjono; Made Oktavia Vidiyanti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2021)
The religiosity construction of the human body in Indonesian poemsThe body is an integral part of being human. It is physical as well as spiritual, not only natural but also supernatural. In this regards, proper treatment of the body may indicate the level of one’s religiosity. The purpose of this study was to find the religiosity of the human body in poems written by Indonesian poets. Adopting Küçükcan’s (2005) religiosity dimension framework, we examine the body's religiosity from the following dimensions: belief, practice, and spirituality. Our data were a collection of language units in lines and stanzas taken from poems written by Mashuri and Alek Subairi. They were analyzed using hermeneutic approach. The results show that within the dimension of belief reflected in the poems, the body is considered mortal and religious. Within the practical dimension, the body is used to fulfill economic necessity. It is also used as a means to meet God. Within the dimension of spirituality, the body channels God’s presence in various forms: love, caringness, and warmth. We conclude that these three religiosity dimensions support and complement each other.Keywords: religiosity, beliefs, practice, spirituality, bodyKonstruksi religiositas tubuh dalam puisi IndonesiaTubuh merupakan bagian penting dalam diri manusia. Tubuh bukan hanya fisik tetapi rohani; tubuh bukan hanya kodrati, tetapi juga adikodrati. Perlakuan terhadap tubuh secara benar menunjukkan kadar religiositas seseorang.  Tujuan penelitian ini adalah untuk menemukan religiositas tubuh pada puisi-puisi karya penyair Indonesia. Religiositas tubuh dikaji dari segi dimensi keyakinan, praktik, dan spiritualitas dengan memakai teori dimensi religiositas yang dikembangkan oleh Küçükcan (2005). Penelitian ini menggunakan data yang berupa satuan bahasa dalam larik dan bait yang terdapat pada puisi Mashuri dan Alek Subairi. Data lalu dianalisis secara hermeneutik. Hasilnya menunjukkan bahwa dalam dimensi keyakinan yang terdapat dalam puisi, tubuh dipandang fana dan religius. Dalam dimensi praktik, tubuh dipakai untuk memenuhi kebutuhan ekonomi dan juga sebagai sarana pertemuan dengan Tuhan. Dalam dimensi spiritualitas, tubuh menjadi sarana kehadiran Tuhan dalam aneka rupa: cinta, kepedulian, dan kehangatan. Ketiga dimensi tersebut saling mendukung dan saling mengisi.Kata Kunci: religiositas, keyakinan, praktik, spiritualitas, tubuh